Mode Dependent Laser Pulse Amplification: A Computational Approach in 3D - Pflaum, Christoph; Springer, Ramon (CLEO 2020, 2020)
We present a numerical simulation technique for short laser pulse amplification in solid-state crystals. It takes into account the full spatial pumping profile by solving the 3-dimensional photon transport and allows to calculate pulse energy accuratel